THE INDIVIDUAL ACADEMIC WORK IN THE VOCATIONAL TRAINING OF PHYSICAL EDUCATION AND SPORT SPECIALISTS - VOLCU, Gheorghe; VOLCU, Irina (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2023)
In this article we approach the topic of individual academic work in the vocational training of specialists of physical education and sport. This activity, very important in the university educational process, is promoted both within classroom hours and outside of them, but most often individual work is promoted within seminars, laboratory hours, projects, practical works, competitions and performing tasks at home. Individual work is one of the main forms of study of subjects by students specializing in physical education and sport, expressed by studying theoretical topics, performing control and laboratory work and applying knowledge to carry out semestrial, periodical and final assessments. Starting from the analysis of references on the mentioned topic and ending with qualitative and quantitative reflections from the specific university context, we highlight the aspect of the individual work of the students from the point of view of professional training. It is carried out for the purpose of students specializing in physical education and sport acquiring general and special professional skills, including the ability to use the knowledge acquired in the professional field. An important result of the individual work of students is the formation of their ability to train individually in order to obtain knowledge, skills, competences for the purpose of continuous professional development. REZUMAT. Lucrul individual academic în formarea profesională a specialiștilor de educație fizică și sport. În acest articol abordăm tema lucrului individual academic în formarea profesională a specialiștilor de educație fizică și sport. Această activitate, foarte importantă în procesul educațional universitar, este promovată atât în cadrul orelor auditoriale, cât și înafara acestora, dar cel mai frecvent lucrul individual se promovează în cadrul seminarelor, a orelor de laborator, a proiectelor, a lucrărilor practice, în cadrul concursurilor și la efectuarea sarcinilor pentru acasă. Lucrul individual este una dintre formele principale de studiu al disciplinelor de către studenții specializați în educație fizică și sport, exprimat prin studierea temelor teoretice, efectuarea lucrărilor de control și de laborator și aplicarea cunoștințelor la susținerea evaluărilor semestriale, periodice și finale. Pornind de la analiza surselor de referință la tema menționată și finalizând cu reflecții calitative și cantitative din contextul universitar specific, evidențiem aspectul lucrului individual al studenților din punct de vedere al pregătirii profesionale. Acesta se desfășoară în scopul dobândirii de către studenții specializați în educație fizică și sport a unor competențe profesionale generale și speciale, inclusiv capacitatea de a utiliza cunoștințele dobândite în domeniul profesional. Un rezultat important al lucrului individual studențesc este formarea la aceștia a capacității de a se instrui individual pentru obținerea de cunoștințe, abilități, competențe în scopul dezvoltării profesionale continue. Cuvinte cheie: Educație fizică și sport, formare profesională, lucru individual, învățământ superior, student, profesor, curriculum. Received 2023 April 03; Revised 2023 June 07; Accepted 2023 June 08; Available online 2023 July 30; Available print 2023 August 30.